Tan Kiaw V. Gan Chye Koon: A Distinction Between A â€œTenancyâ€ And A â€œTenancy Exempt From Registrationâ€? - Khaw, Lake Thee (Journal of Malaysian and Comparative Law, 2019)
Case note on Tan Kiaw V. Gan Chye Koon as to whether there is a distinction between a tenancy and a tenancy exempt from registration.